An effective model for QoS assessment in data caching in MANET environments. (1st January 2013) - Saravanan, N.; Baskaran, R.; Shanmugam, M.; Basha, M.S. Saleem; Paul, P. Victer
In Mobile Ad Hoc Network (MANET), every neighbouring node is likely to have similar interests and need to access the similar data at different times. So, by caching the frequently accessed data item within MANET, it is possible to reduce the cost of accessing the same data from the external source. In this perspective, an effective data cache mechanism is proposed by Paul et al., using the distributed spanning tree as a communication structure to lessen network overload. As an enhancement, ant colony optimisation technique has been applied on DST to cope with the fragile nature of the MANET. In this paper, a theoretical model has been formulated to assess the performance factors such as cooperative cache, mobility and hand-off and routing technique. In addition to these, the performance improvement of DCM in MANET has been proved experimentally using cache hit and data consistency using appropriate simulation.